Rapid Intrinsic Variability of SGR A* at Radio Wavelengths - Yusef-Zadeh, F.; Wardle, M.; Miller-Jones, James; Roberts, D.; Grosso, N.; Porquet, D. (The American Astronomical Society, 2011)
Sgr A* exhibits flares in radio, millimeter, and submillimeter wavelengths with durations of ~1 hr. Using structure function, power spectrum, and autocorrelation function analysis, we investigate the variability of Sgr A* on timescales ranging from a few seconds to several hours and find evidence for subminute timescale variability at radio wavelengths. These measurements suggest a strong case for continuous variability from subminute to hourly timescales. This short timescale variability constrains the size of the emitting region to be less than 0.1 AU. Assuming that the minute timescale fluctuations of the emission at 7 mm arise through the expansion of regions of optically thick synchrotron-emitting plasma, this suggests the presence of explosive, energetic expansion events at speeds close to c. The required rates of mass processing and energy loss of this component are estimated to be 6 × 10–10 M yr–1 and 400 L , respectively. The inferred scale length corresponding to 1 minute light travel time is comparable to the time-averaged spatially resolved 0.1 AU scale observed at 1.3 mm emission of Sgr A*. This steady component from Sgr A* is interpreted mainly as an ensemble average of numerous weak and overlapping flares that are detected on short timescales. The nature of such short timescale variable emission or quiescent variability is not understood but could result from fluctuations in the accretion flow of Sgr A* that feed the base of an outflow or jet.